The Role of Dipeptidyl Peptidase – 4 Inhibitors in Diabetic Kidney Disease - Panchapakesan, Usha; Pollock, Carol (Frontiers in Immunology, 2015)
Despite major advances in the understanding of the molecular mechanisms that underpin the development of diabetic kidney disease, current best practice still leaves a significant proportion of patients with end stage kidney disease requiring renal replacement therapy. This is on a background of an increasing diabetes epidemic worldwide. Although kidney failure is a major cause of morbidity the main cause of death remains cardiovascular in nature. Hence diabetic therapies which are both “cardio-renal” protective seem the logical way forward. In this review we discuss the dipeptidyl peptidase 4 inhibitors which are glucose lowering agents used clinically and their role in diabetic kidney disease with specific focus on renoprotection and surrogate markers of cardiovascular disease. We highlight the novel pleiotropic effects of dipeptidyl peptidase 4 that make it an attractive additional target to combat the fibrotic and inflammatory pathways in diabetic kidney disease and also discuss the current literature on the cardiovascular safety profile of dipeptidyl peptidase 4 inhibitors. Clearly these observed renoprotective effects will need to be confirmed by clinical trials to determine whether they translate into beneficial effects to patients with diabetes.